The Influence of Emotional Intelligence, Intellectual Intelligence and Social Intelligence on Employee Performance in Martapura District, Banjar Regency, Kalimantan Province - Kadir, Abdul; Audah, Ali; Naimah, Naimah; Jahra, Pati Matu; Badrian, Badrian; Syarqawie, Fithriana (Universitas Hang Tuah, 2026)
This study aims to analyze the effect of emotional intelligence, intellectual intelligence, and social intelligence on employee performance at the Martapura Kota District Office, Banjar Regency, South Kalimantan Province. The research employed a quantitative approach using a survey method. The population consisted of all employees at the Martapura Kota District Office, and a census sampling technique was applied. Data were collected through questionnaires using a Likert scale and analyzed using validity and reliability tests, multiple linear regression analysis, simultaneous testing (F-test), and partial testing (t-test) with the assistance of SPSS software. The results indicate that emotional intelligence, intellectual intelligence, and social intelligence simultaneously have a significant effect on employee performance. Partially, each independent variable also has a significant effect on employee performance. The coefficient of determination (R²) of 0.941 indicates that 94.1% of the variance in employee performance can be explained by emotional intelligence, intellectual intelligence, and social intelligence, while the remaining 5.9% is influenced by other factors outside this study. Based on the beta coefficient values, intellectual intelligence is identified as the most dominant variable influencing employee performance. These findings highlight the importance of developing intellectual, emotional, and social intelligence in an integrated manner to improve employee performance in government institutions.